2001
DOI: 10.1002/app.1498
|View full text |Cite
|
Sign up to set email alerts
|

NR–EPDM covulcanization: A novel approach

Abstract: Bis(diisopropyl)thiophosphoryl disulfide (DIPDIS) was used successfully as a novel coupling agent cum accelerator to co-vulcanize the elastomer blend comprising highly unsaturated natural rubber (NR) and ethylene propylene diene rubber (EPDM) of low unsaturation content. The blend vulcanizates produced exhibit improved physical properties that can be further enhanced by implementing a two-stage vulcanization technique, as well as by judicious selection of the NR-to-EPDM ratio. The results indicate coherency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…Typical S-shaped curves ( Figure 3) are obtained in all the cases. It is interesting to note that faster cure rate is observed with silica than with gum 14 and black-filled vulcanizates of similar composition (Figure 1). This difference might be explained by the reaction between the fragments of DIPDIS and the silanol (Si-OH) groups present at the silica surfaces.…”
Section: One-stage Vulcanization Of Silica Filled Compoundsmentioning
confidence: 89%
See 1 more Smart Citation
“…Typical S-shaped curves ( Figure 3) are obtained in all the cases. It is interesting to note that faster cure rate is observed with silica than with gum 14 and black-filled vulcanizates of similar composition (Figure 1). This difference might be explained by the reaction between the fragments of DIPDIS and the silanol (Si-OH) groups present at the silica surfaces.…”
Section: One-stage Vulcanization Of Silica Filled Compoundsmentioning
confidence: 89%
“…In twostage vulcanization, it could be reasonably expected that accelerator fragments get anchored onto the EPDM backbone (Scheme 1), 14 thereby rendering the EPDM more polar because of the pendant moieties of DIPDIS. However, with the …”
Section: Two-stage Vulcanization Of Carbon Black-filled Compoundsmentioning
confidence: 99%
“…On the other hand, it is also expected that DIPDIS will interact with the rubber chain and the silicate particles because of its multifunctional character. Ghosh et al 32 showed an identical reaction mechanism when they treated EPDM with DIPDIS in a silica-filled system. Figure 2 shows the ATR-infrared given for EPDM-gum and EPDM-clay nanocomposites.…”
Section: Atr Spectroscopymentioning
confidence: 93%
“…When nanolayers have been exfoliated, the improvement in properties can be seen as an increase in tensile properties, as well as enhanced barrier properties, decreased solvent permeability, and increased thermal stability and flame retardance. [6], [7].…”
Section: Introductionmentioning
confidence: 99%